Potensi Bunga Cempaka Kuning Magnolia champaca (L.) Baill. Ex Pierre Sebagai Antiinflamasi - Hayatillah, Raudhah; Hapsari, Widie Kemala (University of Mataram, 2024)
Yellow champaca is a family of Magnoliaceae, which is designated as the identity of the Nanggroe Aceh Darusalam area, known as Bungong Jeumpa. Yellow champaca contains phytochemicals which can act as antioxidants and can act as an anti-inflammatory, so yellow champaca is widely used as a medicinal plant. Compounds contained in yellow chrysanthemum such as tannins, flavonoids, alkaloids, saponin, sterols and others can act as anti-inflammatories by inhibiting the action of inflammatory media which play a role in the process of inflammation. Yellow champaca is scientifically proven to have anti-inflammatory benefits. Present studi is a compilation of several aspects the indicate that Yellow champaca has potential as an anti-inflammatory which was tested based on content of secondary metabolite compounds.